A toxicological evaluation of a fulvic and humic acids preparation - Murbach, Timothy S.; Glávits, Róbert; Endres, John R.; Clewell, Amy E.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Pasics Szakonyiné, Ilona (Toxicology reports, 2020)
[Display omitted] •Toxicological evaluations of blk. 333 according to OECD guidelines were negative.•Blk. 333 was not mutagenic in vitro and showed no in vivo genotoxic activity.•The NOAEL of the 90-day study was 2000 mg/kg bw/d blk. 333—the highest dose tested.•No target organs or treatment-related toxicological effects were identified.•Our results are relevant to a safety assessment of human ingestion of blk. 333. Humic substances are ubiquitous in soils and waters. These complex superstructures are derived from the decomposition of dead plant and animal matter and are vital to soil health. Their heterogenous composition is specific to their site of origin and is comprised of weakly bound aggregates of small organic compounds that can sequester minerals and make them available to plants. As such, they may possess potential nutritional value for humans, and extractions of fulvic and humic acids can be produced that could be suitable for such purposes. For this reason, we evaluated the toxicological profile of a specific preparation (blk. 333) of fulvic and humic acids derived from a lignite deposit in Alberta, Canada and found it to lack genotoxic potential in a bacterial reverse mutation test, in vitro mammalian chromosomal aberration test, and in vivo mammalian micronucleus test. No general or organ toxicity was observed in Wistar rats following 90 days of continuous exposure, and a no observed adverse effect level (NOEAL) was determined at 2000 mg/kg bw/day, the highest tested dose. Our results suggest the feasibility of further evaluation for development of the preparation as a nutritional supplement in food.